Accuracy improvement of the atmospheric neutrino flux prediction using observed muon spectra at mountain altitude. (February 2020) - Honda, Morihiro; Sajjad Athar, M.; Kajita, Takaaki; Kasahara, Katsuaki; Midorikawa, Shoichi; Nishimura, Jun
Abstract: By the study of the variations of the atmospheric neutrino and muon fluxes, due to that of the hadronic interaction, we find that when have accurate atmospheric muon flux data, we can estimate the prediction error of the atmospheric neutrino flux calculating with the same interaction model from the residual. However, the relation of the residual of the muon flux and the error in the neutrino flux is largely dependent on the observation site of the muon flux. We study this relation at several observation sites, near Kamioka at sea level, same but 2770m a.s.l.., Hanle India (4500m a.s.l.), and at Balloon altitude (~ 32km).